Heat stroke with sepsis: A case report and review of the literature - Suyu Wei; Liang Sun (Journal of International Medical Research)
Heat stroke, triggered by excessive heat exposure or intense physical activity, is a medical condition characterized by a rapid rise in core body temperature, central nervous system dysfunction and multiorgan failure. A patient presented with heat stroke and was unconscious. During treatment, we identified a range of complications, including shifted flora, coagulation abnormalities, liver damage and renal failure—indicating multiorgan dysfunction. We administered antibiotic therapy, blood purification and other comprehensive treatments, leading to the patient’s recovery and subsequent discharge. For cases of heat stroke in an intensive care setting, clinicians must recognize the condition early and act swiftly to reduce body temperature. Additionally, the early use of antibiotics can help prevent microbial imbalance. For eligible patients, hemodialysis should be initiated promptly to manage renal complications effectively.